2017
DOI: 10.1155/2017/4631751
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Performance and Rotor Tip Flow Field in a Low Speed Research Compressor with Circumferential Groove Casing Treatment at Varying Tip Clearance

Abstract: Experimental investigations in a single-stage low speed axial research compressor are presented. The influence of four different rotor tip clearances on the overall compressor performance and on the rotor tip flow field is investigated in configurations with and without circumferential groove casing treatments. Piezo-resistive pressure transducers are used to capture the unsteady flow field in the rotor tip region. The investigated casing groove is effectively working at the three largest investigated tip clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…As the tip gap extends, a hump in the FFT spectra of the throttled operating points becomes prominent, while at the design point (Φ = 0.57), no change is detectable. The frequency of the hump is about 1/2 BPF for s/C = 2.6% and reduces to around 1/3 BPF for s/C = 4.3%, which corresponds to the previous observation in the other tests based on the LSRC [2,7]. Such unsteady disturbances indicated by the narrow-band region below the BPF are believed to be the RIs.…”
Section: Overall Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…As the tip gap extends, a hump in the FFT spectra of the throttled operating points becomes prominent, while at the design point (Φ = 0.57), no change is detectable. The frequency of the hump is about 1/2 BPF for s/C = 2.6% and reduces to around 1/3 BPF for s/C = 4.3%, which corresponds to the previous observation in the other tests based on the LSRC [2,7]. Such unsteady disturbances indicated by the narrow-band region below the BPF are believed to be the RIs.…”
Section: Overall Performancesupporting
confidence: 86%
“…The RIs were found in those configurations with relatively large tip clearance. Rolfes et al [7] observed RI in a single stage build of the Dresden LSRC when the rotor tip clearance was increased to 2.5% chord length, and the mean frequency of the hump decreased with the tip gap extended. The amplitudes of RIs were damped by a circumferential groove casing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The change in tip clearance affects not only the rotor performance but also the downstream stator performance and the stability of the stage [15][16][17][18]. Howard and Puterbaugh [19] combined computational fluid dynamics(CFD) unsteady simulation calculations and experiments to study the effect of the tip clearance variation on the efficiency of the transonic small aspect ratio (average rotor aspect ratio = 0:57) axial compressor stage.…”
Section: Introductionmentioning
confidence: 99%